Economics at the Threshold of Two Centuries - Martišius, Stanislovas (Ekonomika, 2003)
The publication discusses the alteration of economic thoughts at the and of 20th century. It shows how the theoretic economic thought gradually relocates to USA, the very science of economics becomes more and more specialised and integrates with other social sciences (politology, history, law, sociology); mathematical methods become the core to theoretical and applied economics; new research trends like experimental economics, psychology of economics theory of public option have evolved. The publication suggests to establish faculties of social sciences in the main Lithuanian universities and economic profile science institutions of university stature. In authors view, this would set the Lithuanian economics and studies to the European standards.